B‐cell depletion limits HTLV‐1‐infected T‐cell expansion and ameliorate HTLV‐1‐associated myelopathy - Aowei Lv; Yaofeng Fang; Xiaohong Lin; Jiaying Chen; Huanhuan Song; Ning Wang; Wan‐Jin Chen; Ying Fu; Rui Li; Yi Lin (Annals of Clinical and Translational Neurology)
Abstract Objective Human T‐cell leukemia virus type 1‐associated myelopathy (HAM) is a chronic, progressive, inflammatory disease with unclear pathogenesis and no effective treatments. We aimed to investigate a novel mechanistic theory and treat HAM patients with rituximab, which can deplete CD20+ B lymphocytes in circulation. Methods Single‐cell RNA sequencing (scRNA‐seq) data was analyzed to identify HTLV‐1‐associated B cells and their effect on T cells. An observational analysis of our HAM cohort was conducted to elucidate changes in the immunological microenvironment of these patients. Peripheral blood mononuclear cells (PBMC) from HAM patients were isolated to explore the efficacy of B cell depletion in vitro. To assess the effect of B‐cell depletion on HAM patients, eligible participants in our cohort received rituximab therapy (NCT04004819). Results ScRNA‐seq results suggest a significant effect of HTLV‐1‐associated B cells on T cells. Additionally, HTLV‐1 was found to infect B cells and depletion of B cells inhibited the proliferation of T cells. Number of B cells in HAM patients had positive correlation with the proviral load and infected cell counts. Depletion of B cells led to a reduction in HTLV‐1 proviral load in vitro. Furthermore, in clinical trial, 14 HAM patients were enrolled. Three patients (21.4%) who received rituximab failed to achieve remission, compared to 24 (85.7%) patients received any other therapy that failed to achieve remission. With a low level of circulating B cells, the proportion of Ki67‐positive cells in CD4+ T cells fell. Interpretation This study provided evidence that depleting B‐lymphocytes is an innovative strategy for treating patients with HAM and broadens the understanding of the role of B cells in infectious immunity.